A phase 2 study of bortezomib in combination with ifosfamide/vinorelbine in paediatric patients and young adults with refractory/recurrent Hodgkin lymphoma: a Children's Oncology Group study. (1st April 2015) - Horton, Terzah M.; Drachtman, Richard A.; Chen, Lu; Cole, Peter D.; McCarten, Kathleen; Voss, Stephan; Guillerman, Robert P.; Buxton, Allen; Howard, Scott C.; Hogan, Shirley M.; Sheehan, Andrea M.; López‐Terrada, Dolores; et al.
Summary A Children's Oncology Group clinical trial aimed to determine if bortezomib (B) increased the efficacy of ifosfamide and vinorelbine (IV) in paediatric Hodgkin lymphoma (HL). This study enrolled 26 relapsed HL patients (<30 years) treated with two to four cycles of IVB. The primary endpoint was anatomic complete response (CR) after two cycles. Secondary endpoints included overall response (OR: CR + partial response) at study completion compared to historical controls [72%; 95% confidence interval (CI): 59–83%]. Although few patients achieved the primary objective, OR with IVB improved to 83% (95% CI: 61–95%; p = 0·32). Although not statistically different, results suggest IVB may be a promising combination.